Platinum(ii) complexes of mixed-valent radicals derived from cyclotricatechylene, a macrocyclic tris-dioxolene. Issue 12 (7th September 2015) - Loughrey, Jonathan J.; Patmore, Nathan J.; Baldansuren, Amgalanbaatar; Fielding, Alistair J.; McInnes, Eric J. L.; Hardie, Michaele J.; Sproules, Stephen; Halcrow, Malcolm A.
Abstract : The redox series[1] 0/1+/2+/3+ has been characterised by UV/vis/NIR spectroelectrochemistry, cw EPR, ENDOR and HYSCORE spectroscopies and DF calculations. Abstract : Three complexes of cyclotricatechylene (H6 ctc), [{PtL}3 (μ3 -ctc)], have been synthesised: (L = 1, 2-bis(diphenylphosphino)benzene {dppb}, 1 ; L = 1, 2-bis(diphenylphosphino)ethane {dppe}, 2 ; L = 4, 4′-bis( tert -butyl)-2, 2′-bipyridyl { t Bu2 bipy}, 3 ). The complexes show three low-potential, chemically reversible voltammetric oxidations separated by ca. 180 mV, corresponding to stepwise oxidation of the [ctc] 6− catecholato rings to the semiquinonate level. The redox series[1] 0/1+/2+/3+ and[3] 0/1+/2+/3+ have been characterised by UV/vis/NIR spectroelectrochemistry. The mono- and di-cations have class II mixed valent character, with reduced radical delocalisation compared to an analogous bis-dioxolene system. The SOMO composition of[1˙] + and[3˙] + has been delineated by cw EPR, ENDOR and HYSCORE spectroscopies, with the aid of two monometallic model compounds [PtL(DBsq˙)] + (DBsqH = 3, 5-bis( tert -butyl)-1, 2-benzosemiquinone; L = dppe or t Bu2 bipy). DF and time-dependent DF calculations confirm these interpretations, and demonstrate changes to spin-delocalisation in the ctc macrocycle as it is sequentially oxidised.